(untitled) (Research, Society and Development, 2020)
Introduction: The training of nurses today raises the need for new training paths, in which the integration of teaching and extension is shown to be a favorable strategy for professional training. Objective: To understand how the integration of teaching and extension has had an impact on the training of extension students in the ACOLHER Program. Method: This is an exploratory study with a qualitative approach. The setting was the ACOLHER Extension Program, with nine students participating in the study, two scholarship holders and seven volunteers, members of the program, with data collection through a focus group. Results: For extension workers, the integration of teaching and extension is favorable to the improvement of the knowledge learned at the University and allows the exercise of autonomy, responsibility and interpersonal relationships. They consider the nursing consultation favorable to the practice of the nursing process and regarding the playful activities they allow the improvement of the pedagogical conceptions and group processes that involve health education. Final considerations: Extramural activities, like extension projects, are favorable spaces for academic training when considering autonomy, initiative, critical-reflexive action and overcoming fragmented teaching as beacons for the performance of students in Proposed activities.